The reality of change management and its impact on the development of NGO business in Makkah - Alsabban, Mona Mohammad; Al-Nimri, Hanan Sarhan (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed at investigate the reality of change management and its impact in the development of NGO, by identifying the importance of managing change in the work of NGOs, identifying the availability of change management in their work, and then identifying the impact of change management in the development of NGO business. To achieves these objectives, the researcher used the descriptive method and the resolution information collection Tool was built in four main axes, related to the research objectives, and the questionnaire was applied to a sample of (40) samples of managers and staff in non-governmental organizations, and after analyzing and processing the data statistically, the study produced many results, the most important of which was There is a very high level of staff knowledge of the importance of change in organizations Average value of (4, 38), a high level of management of change in organizations Average value of (3, 98), obstacles to managing change in organizations Average value of (4, 18), and a high impact on the management of change in NGOs Average value of (4, 19), and in light of the results of the study recommended that the change in the organization be clearly defined in accordance with the requirements of work and the need to determine the authority and responsibility for this change, and the need for management to deal with employees positively and concern for human relations.